Absence From Work And Its Impact On The Professional Stability Of The Employees Of Sports Institutions - Karbi , Moussa; Bafa , Abdullah (sports creativity, 2025)
This study aims to find out the impact of absenteeism on the professional stability of the employees of sports institutions in the employees of the Directorate of Youth and Sports of the Wilayat of Messila. In this study, we used the descriptive approach that is the most appropriate for this study. As for the study community, we selected 45 individuals, including30 individuals, to conduct the basic study. I designed a questionnaire consisting of two axes: the income axis and the promotion axis. At the end of this study, we concluded that the wage is the first determinant of the workers' sense of professional stability, as most workers show a great desire to change their position for other more paid positions, and workers consider that reaching the career they aspire to will only be through obtaining the opportunity for promotion.